Decreased Maturation of Dendritic Cells in the Central Airways of COPD Patients Is Associated with VEGF, TGF-β and Vascularity - Zanini, Andrea; Spanevello, Antonio; Baraldo, Simonetta; Majori, Maria; Della Patrona, Sabrina; Gumiero, Federico; Aiello, Marina; Olivieri, Dario; Saetta, Marina; Chetta, Alfredo (Respiration, 2014)
Background: Dendritic cells (DCs) have a pivotal role in the onset and regulation of innate and adaptive immune responses. Moreover, DCs can interact with angiogenic modulators, resulting in modification of their biology and participation in angiogenesis. Objectives: This study was designed to evaluate the relationship between the density of DCs, vascularity and expression of angiogenic factors [vascular endothelial growth factor (VEGF), transforming growth factor (TGF)-β and basic fibroblast growth factor (bFGF)] in the central airways of chronic obstructive pulmonary disease (COPD) patients. Methods: The study included 20 patients with moderate/severe COPD and 8 healthy control subjects. Bronchial biopsies were evaluated by immunohistochemistry. Specimens were examined for CD83 and CD207 to mark mature and immature DCs, respectively, for collagen IV to evaluate vascularity, and for VEGF, TGF-β and bFGF. Results: Compared to controls, COPD patients had a significant reduction of CD83+ cells and an increased CD207/CD83 ratio (p < 0.05). Vascularity, VEGF, TGF-β and bFGF were also significantly increased in COPD patients as compared to controls (p < 0.01). In COPD patients, CD83+ cells were inversely related to VEGF and TGF-β expression (p < 0.05). Moreover, the CD207/CD83 ratio was positively related to VEGF, TGF-β and vascularity (p < 0.05). Finally, CD207+ cells were inversely related to FEV 1 (p < 0.05). Conclusion: Our results show a reduced maturation of DCs in COPD that was related to airway vascularity and angiogenic factors (VEGF and TGF-β). Additionally, immature DCs were significantly related to disease severity. We propose that the interplay between airway vascular changes, on one hand, and DCs maturation on the other, may play a key role in the pathogenetic mechanisms of COPD.